2011
DOI: 10.1128/jcm.00083-11
|View full text |Cite
|
Sign up to set email alerts
|

Activity of TDT 067 (Terbinafine in Transfersome) against Agents of Onychomycosis, as Determined by Minimum Inhibitory and Fungicidal Concentrations

Abstract: TDT 067 is a novel carrier-based dosage form (liquid spray) of 15 mg/ml of terbinafine in Transfersome that has been developed to deliver terbinafine to the nail bed to treat onychomycosis. In this study, we report the in vitro activities of TDT 067 against dermatophytes, compared with those of the Transfersome vehicle, naked terbinafine, and commercially available terbinafine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Perhaps the use of a more innovative delivery vehicle would generate a clearer picture of the effectiveness of dual therapy. For example Ghannoum et al (2011) have incorporated terbinafine within transfersomes (described by Ghannoum et al as "carrier vehicles [consisting of] responsive, composite lipid aggregates that are highly deformable and have high surface hydrophilicity") and demonstrated that such vehicles, at an active concentration of 1.5% (w/v), were considerably more potent (with MIC 50 values against Trichophyton rubrum and Tricophyton mentagrophytes being 30-fold and 60-fold lower, respectively) than a 1% terbinafine spray in vitro.…”
Section: Current Approaches and Clinical Evidencementioning
confidence: 98%
“…Perhaps the use of a more innovative delivery vehicle would generate a clearer picture of the effectiveness of dual therapy. For example Ghannoum et al (2011) have incorporated terbinafine within transfersomes (described by Ghannoum et al as "carrier vehicles [consisting of] responsive, composite lipid aggregates that are highly deformable and have high surface hydrophilicity") and demonstrated that such vehicles, at an active concentration of 1.5% (w/v), were considerably more potent (with MIC 50 values against Trichophyton rubrum and Tricophyton mentagrophytes being 30-fold and 60-fold lower, respectively) than a 1% terbinafine spray in vitro.…”
Section: Current Approaches and Clinical Evidencementioning
confidence: 98%
“…It is a potential treatment option for toenail onychomycosis which is still under trial for safety and efficacy. 151,152 ME1111 acts by inhibiting succinate dehydrogenase, an enzyme in the electron transport chain, which in turn affects ATP production in fungal cells. It has a small molecular size and has higher penetration capacity in the nail plate than ciclopirox.…”
Section: Novel Topical Therapiesmentioning
confidence: 99%
“…In vitro experiments have demonstrated that TDT 067 has potent inhibitory and cidal activity against dermatophytes and has enhanced antifungal activity compared to that of conventional terbinafine preparations (10). The excipients of TDT 067 are widely used in pharmaceutical and cosmetic products for topical application, and clinical studies involving more than 2,000 patients with different diseases have shown that Transfersome preparations are well tolerated (2,16,22).…”
mentioning
confidence: 99%